-2(-2y+1)=-2y+22

Simple and best practice solution for -2(-2y+1)=-2y+22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-2y+1)=-2y+22 equation:


Simplifying
-2(-2y + 1) = -2y + 22

Reorder the terms:
-2(1 + -2y) = -2y + 22
(1 * -2 + -2y * -2) = -2y + 22
(-2 + 4y) = -2y + 22

Reorder the terms:
-2 + 4y = 22 + -2y

Solving
-2 + 4y = 22 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-2 + 4y + 2y = 22 + -2y + 2y

Combine like terms: 4y + 2y = 6y
-2 + 6y = 22 + -2y + 2y

Combine like terms: -2y + 2y = 0
-2 + 6y = 22 + 0
-2 + 6y = 22

Add '2' to each side of the equation.
-2 + 2 + 6y = 22 + 2

Combine like terms: -2 + 2 = 0
0 + 6y = 22 + 2
6y = 22 + 2

Combine like terms: 22 + 2 = 24
6y = 24

Divide each side by '6'.
y = 4

Simplifying
y = 4

See similar equations:

| 0.7-b=1.9 | | R/15=30 | | -1-5/8-8 | | 5(2c-3)=2c+5 | | 8n=n+42 | | X+Y=231 | | x+2=-2x-14 | | 16x-92=180 | | 5=x+31 | | -4-(-4)/3-6 | | 10y=-8 | | -324=27s | | (14x+7)-(-3x+2)= | | 4(3z-3)=9z-7 | | X+11x=156 | | 4x+8(-3x-3)=3 | | 12*48= | | 3-2/6-3 | | 25x^3y^4+50x^3y^4-75x^2y^3=0 | | x^2=2x-21 | | 3/4k-28=4 | | (12*4)+16= | | 3(2p+7)=82+x | | 8(-9+3)=6(-9+1) | | 9x+63=180 | | 4x-2(-2x-4)=3x-10+5x | | 1-(-1)/-6-4 | | 13x=16y+1 | | K-311=203 | | d-3.4=-9.3 | | 2x^6+4x^4+8x=0 | | 8(x+3)=6(x+1) |

Equations solver categories